An update on osteoporosis research: effect of calcium plus vitamin D supplementation - Shill, Lincon Chandra; Purba, Nafisa Habib; Sultana, Marjia; Hasan, Towhid; Rahman, Mahmudur; Sultana, Nahid (International Journal Of Community Medicine And Public Health, 2019)
Osteoporosis is the most common systemic skeletal disease characterized by increased bone fragility. There lies an incongruity among research regarding combined supplementation of calcium (Ca) plus vitamin D and loss of bone health. Hence, the present review is aimed to highlight the current development of osteoporosis research and try to solve the inconsistency among the present knowledge. Electronic databases like PubMed, Cochrane Library, and EMBASE were searched from their inception to December 2018 using terms “calcium,” “vitamin D,” and “osteoporosis.” A systemic approach was followed to reach a final of 23 studies assessing the synergetic effect of calcium and vitamin D on osteoporosis and fractures risk. Among the included studies, nineteen have revealed that calcium and vitamin D decrease bone resorption, reduce the incidence of fractures, increase bone mineral density (BMD) and overall bone health. However, no significant osteogenic response was reported in five trials after supplementation with calcium and vitamin D together. Osteoporosis results in a reduced quality of life, increased disability-adjusted life span, and big economic burden to health care systems of countries. Early diagnosis before the occurrence of fractures and by assessing BMD and with early treatment, osteoporosis can be prevented. It is not entirely possible to draw a conclusion regarding beneficial effects of calcium plus vitamin D supplementation; future research based on the fundamentals of bone biology focusing on molecular genetics, and influencing factors of the acquisition of bone mass during growth and bone loss can alleviate present controversies.